Performance Evaluation of Optimal Ate Pairing on Low-Cost Single Microprocessor Platform - Pesonen, Mikko (My University, 2020)
The framework of low-cost interconnected devices forms a new kind of cryptographic environment with diverse requirements. Due to the minimal resource capacity of the devices, light-weight cryptographic algorithms are favored. Many applications of IoT work autonomously and process sensible data, which emphasizes security needs, and might also cause a need for specific security measures. A bilinear pairing is a mapping based on groups formed by elliptic curves over extension fields. The pairings are the key-enabler for versatile cryptosystems, such as certificateless signatures and searchable encryption. However, they have a major computational overhead, which coincides with the requirements of the low-cost devices. Nonetheless, the bilinear pairings are the only known approach for many cryptographic protocols so their feasibility should certainly be studied, as they might turn out to be necessary for some future IoT solutions. Promising results already exist for high-frequency CPU:s and platforms with hardware extensions. In this work, we study the feasibility of computing the optimal ate pairing over the BN254 curve, on a 64 MHz Cortex-M33 based platform by utilizing an optimized open-source library. The project is carried out for the company Nordic Semiconductor. As a result, the pairing was effectively computed in under 26* 10^6 cycles, or in 410 ms. The resulting pairing enables a limited usage of pairing-based cryptography, with a capacity of at most few cryptographic operations, such as ID-based key verifications per second. Referring to other relevant works, a competent pairing application would require either a high-frequency - and thus high consuming - microprocessor, or a customized FPGA. Moreover, it is noted that the research in efficient pairing-based cryptography is constantly taking steps forward in every front-line: efficient algorithms, protocols, and hardware-solutions.
Keywords: pairing-based cryptography, embedded platform, optimal ate pairing